2017
DOI: 10.12973/eurasia.2017.01213a
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Organizational Trust On Organizational Learning And Creativity

Abstract: In the knowledge economy era, the competitive advantage of an enterprise is established on intangible resources and capability. Trust allows individuals acquiring and exchanging intellectual capitals, especially in ambiguous and uncertain situations, and knowledge exchange relies on the existence of trust. Different from past other industries, hi-tech industry stresses on intangible assets, endeavors to transform real assets into valuable knowledge, and manage and create "intellectual property" based on value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The findings showed that organizational trust is critical for PAS indicating that the relationship is positive and the increase in organizational trust will result in a positive increase in the PAS in Jordan. Having a high level of organizational trust will lead to a positive increase in the performance of employees as shown in various findings of previous studies (Jiang & Chen, 2017;Naami & Hashemi, 2020;Sharkie, 2009;Yılmaz, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…The findings showed that organizational trust is critical for PAS indicating that the relationship is positive and the increase in organizational trust will result in a positive increase in the PAS in Jordan. Having a high level of organizational trust will lead to a positive increase in the performance of employees as shown in various findings of previous studies (Jiang & Chen, 2017;Naami & Hashemi, 2020;Sharkie, 2009;Yılmaz, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Organizational justice can promote a positive organizational learning culture (Chan & Lai, 2017;Donglong et al, 2020). This can lead to increased knowledge sharing and collaboration, which are critical organizational learning aspects (Jiang & Chen, 2017). A study by Wahda et al (2020) suggests that organizational justice significantly and favorably impacts organizational learning.…”
Section: Organizational Learning Mediation In the Relationship Betwee...mentioning
confidence: 99%
“…According to Song et al (2011), creativity in organisational learning may improve the organization’s and individuals’ efficiency. Jiang and Chen (2017) established a strong link between knowledge and organisational innovation in the organisational learning process. According to Hamdani and Susilawati (2018), learning may help a company become more innovative.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%